Applications of ionic liquids in soil remediation: Mechanisms, efficiency and life cycle assessment - Shams Razzak Rothee; Hamed Heidari; Marie-Odile Fortier; Eakalak Khan (Elsevier, 2024)
Ionic liquids (ILs) are eco-friendly substitutes for volatile organic solvents due to their unique properties, fostering widespread adoption across academic fields and industries. This review critically evaluates their application in soil remediation, comparing their performance and environmental footprint against conventional soil remediating agents. The review provides insights into the interplay of IL characteristics, optimal environmental conditions, and contaminant removal mechanisms, while also exploring strategies for modifying and regenerating ILs. Optimal conditions for contaminant removal involve acidic pH for organic compounds and metals, with high temperatures proving beneficial for metal extraction. ILs remove organic contaminants from soil via electrostatic attraction and π-π interactions. In contrast, heavy metal extraction is facilitated by forming complexes through hydrogen bonding, coordination bonding, and electrostatic interactions. The incorporation of acetone and calcium chloride reduces the viscosity while sodium azide effectively prevents microbial degradation of ILs. Using magnetic ILs, acid elution, ultrasonication, and supercritical CO2 extraction techniques enhances IL regeneration efficiency and facilitates their reuse, thereby minimizing secondary pollution and reducing cost. Life cycle assessment of common ILs for remediation, such as 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim][BF4]) and 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim][PF6]) showed that producing 1 ​kg of [Bmim][BF4] emits 6.75 ​kg CO2, whereas manufacturing 1 ​kg of [Bmim][PF6] releases 5.70 ​kg CO2, indicating [Bmim][PF6] has a lower global warming potential due to its environmentally-friendly precursors. The review advocates for continuous improvements in production processes and the development of ILs synthesized from renewable sources to mitigate environmental impacts and enhance their suitability for soil remediation.